ANALISIS PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN PERBANKAN - Paradito Silverio; Suyatmin Waskito Adi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the effect of financial ratios on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. Financial performance is measured using Return on Assets (ROA), while the financial ratios used include Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), and Operating Costs to Operating Income (BOPO). The research method used is quantitative with an associative approach. The data used are secondary data in the form of annual financial reports from 43 banking companies selected through a purposive sampling method, resulting in 172 observations during the study period. The data analysis technique was carried out using multiple linear regression tests using SPSS software. The results of the study showed that partially the NPL, LDR, and BOPO variables had a significant effect on ROA. While the CAR and NIM variables did not have a significant effect on ROA. Simultaneously, all independent variables have a significant effect on ROA with a significance value of 0.001 and an Adjusted R Square value of 0.806, which means that the model can explain the dependent variable by 80.6%. This finding indicates that certain financial ratios can be used as important indicators in assessing the financial performance of banking in Indonesia.